2017
DOI: 10.1097/aci.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis in preservatives: current standing and future options

Abstract: Given the high rates of sensitization reported over the last years, timely regulatory actions are urgently required for some preservatives that currently represent a concern for public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 44 publications
0
46
0
11
Order By: Relevance
“…Parabens are preservatives that may be a cause of contact hypersensitivity, although this is still controversial. [1][2][3][4] In addition to a direct role as allergens, it should be noted that some forms of paraben could act as adjuvants during sensitization to other allergens. Parabens commonly used as preservatives have a short side chain such as methyl, ethyl, propyl, and BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parabens are preservatives that may be a cause of contact hypersensitivity, although this is still controversial. [1][2][3][4] In addition to a direct role as allergens, it should be noted that some forms of paraben could act as adjuvants during sensitization to other allergens. Parabens commonly used as preservatives have a short side chain such as methyl, ethyl, propyl, and BP.…”
Section: Discussionmentioning
confidence: 99%
“…1) Retrospective studies involving skin patch test in Europe revealed that the proportion of adults sensitized to paraben mixtures exceeded 1% of subjects, 2) however, a more recent similar study suggested that sensitization to parabens is rare. 3) To summarize the current situation, the skin sensitization potency of preservatives is gaining increasing attention while the prevalence of contact allergies to parabens has remained unchanged over the last decade. 4) Besides direct sensitization to parabens, parabens may enhance the sensitization to other allergens.…”
mentioning
confidence: 99%
“…1 The maximum authorized concentrations are 0.02% and 0.01% in rinse-off and leave-on cosmetic products, respectively, and there is an even lower limit of 0.0075% in deodorants and antiperspirants. 5 This difference in sensitization rates between Europe and the United States can be attributed to differences in cosmetic regulations, but also to the use of different patch test concentrations 6 : whereas the recommended test concentration of IPBC in Europe has been 0.2% pet. 2 IPBC is a small, water-soluble molecule that readily penetrates the skin, shows marginal irritant properties, and is considered to have a low sensitizing potential.…”
Section: Introductionmentioning
confidence: 99%
“…the positive patch test reactions to IPBC in iodine-allergic subjects were potentially caused by free iodine released from this preservative agent. However, in contrast to what is seen with iodine and PVP-I, irritant reactions are less likely with IPBC 0.2% pet., certainly compared to the 0.5% preparation 6. IPBC use concentrations have consequently been limited, and it cannot be used in oral and lip products, body lotions, and creams, or in products for children aged <3 years, except in bath products, shower gels, and shampoos.…”
mentioning
confidence: 99%
“…Contact sensitization rates for iodopropynyl butylcarbamate have been reported to range from 1.2% to 4.2%. 6,12 The natural skin care movement's intolerance of parabens and other safer preservatives has unintended consequences, such as the use of more allergenic preservatives such a methylisothiazolinone. This unwarranted avoidance of low-allergen and safe preservatives and increased use of botanicals has been associated with a new epidemic of contact dermatitis, which is responsible for high medical bills, time away from work and family, and a diminished quality of life.…”
mentioning
confidence: 99%